2011
DOI: 10.1523/jneurosci.4572-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortex Encodes the Perceptual Interpretation of Ambiguous Sound

Abstract: The confounding of physical stimulus characteristics and perceptual interpretations of stimuli poses a problem for most neuroscientific studies of perception. In the auditory domain, this pertains to the entanglement of acoustics and percept. Traditionally, most study designs have relied on cognitive subtraction logic, which demands the use of one or more comparisons between stimulus types. This does not allow for a differentiation between effects due to acoustic differences (i.e., sensation) and those due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
128
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(152 citation statements)
references
References 41 publications
21
128
2
Order By: Relevance
“…Thus, the findings here may indicate that Broca's area and the SMG use different spatial scales (intervoxel vs intravoxel, respectively) to process speech inputs. Recently, MVPA studies have shown distributed neural patterns for speech perception within large expanses of the temporal lobes (Formisano et al, 2008;Kilian-Hütten et al, 2011). One possible reason for the discrepancy between our main findings and those of previous studies is that auditory representations of phonemes are coded by patterns of activity distributed across large expanses of temporal cortex, while frontal representations are coded in patterns across smaller expanses.…”
Section: Possible Roles Of Broca's Area In Speech Perceptioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the findings here may indicate that Broca's area and the SMG use different spatial scales (intervoxel vs intravoxel, respectively) to process speech inputs. Recently, MVPA studies have shown distributed neural patterns for speech perception within large expanses of the temporal lobes (Formisano et al, 2008;Kilian-Hütten et al, 2011). One possible reason for the discrepancy between our main findings and those of previous studies is that auditory representations of phonemes are coded by patterns of activity distributed across large expanses of temporal cortex, while frontal representations are coded in patterns across smaller expanses.…”
Section: Possible Roles Of Broca's Area In Speech Perceptioncontrasting
confidence: 99%
“…P, posterior; A, anterior; L, left; R, right. Poldrack, 2007;Desai et al, 2008;Hutchison et al, 2008;Chang et al, 2010;Zevin et al, 2010;Kilian-Hütten et al, 2011). Nevertheless, theories implicating sensorimotor mapping in speech sound categorization (Devlin and Aydelott, 2009) suggest frontal regions should be involved as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral posterior part of HG and the posteriorly adjacent areas have previously been shown to code perceptual states rather than purely acoustic differences of sounds (Kilian-Hütten et al, 2011). Furthermore, these areas have been used to reliably decode speaker information from natural and variable speech sounds .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that multivoxel pattern analysis (MVPA) is sensitive to changes in distributed activation patterns in absence of changes in overall activation level (Haxby et al, 2001). This method has been successfully used to reveal subtle differences in overlapping sound representations Staeren et al, 2009) and purely perceptual processes in the visual (Li et al, 2007(Li et al, , 2009) and auditory (Kilian-Hütten et al, 2011) domain.…”
Section: Introductionmentioning
confidence: 99%